Analisis Teologis terhadap Relasi Manusia Dengan Allah dan Sesamanya dalam Konsep Imago Dei Karl Barth Kejadian 1:26-28 - Tirsa Tudang (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2025)
In the Christian tradition, the concept of imago Dei shows that humans are created in the image and likeness of God, and also humans have a relationship with God that reflects the divine relationship as well as the ontological relationship, in which God as the Creator has a higher position than His creation. humans as social creatures cannot fully reflect the image of God without interacting with each other. The relationship includes aspects of mutual respect and community that reflect the relational nature of divinity. this relationship is multidimensional, involving interrelated spiritual, social, and moral aspects. The human person stands and is centered in the Christian reality that God created in the image and likeness of God and in the essence of God, which has been repeatedly stated that He is the ally of Israel, or the ally of His people. According to the order of creation, man is at the peak of his creative work, whereas the scriptures also tell of the fulfillment and perfection of mankind. Therefore, the subjects of Christianity are God and His people. Christian faith is not only about God, but also about the people of God. God's people are not only the nation of Israel, but all of humanity. It turns out that the description of man can be said to be as old as the existence of man himself. Where does man come from, where does he go, and what is the secret of his life? Of coursem.